Jaya: An Advanced Optimization Algorithm and its Engineering Applications - Venkata Rao, Ravipudi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces readers to the "Jaya" algorithm, an advanced optimization technique that can be applied to many physical and engineering systems. It describes the algorithm, discusses its differences with other advanced optimization techniques, and examines the applications of versions of the algorithm in mechanical, thermal, manufacturing, electrical, computer, civil and structural engineering. In real complex optimization problems, the number of parameters to be optimized can be very large and their influence on the goal function can be very complicated and nonlinear in character. Such problems cannot be solved using classical methods and advanced optimization methods need to be applied. The Jaya algorithm is an algorithm-specific parameter-less algorithm that builds on other advanced optimization techniques. The application of Jaya in several engineering disciplines is critically assessed and its success compared with other complex optimization techniques such as Genetic Algorithms (GA), Particle Swarm Optimization (PSO), Differential Evolution (DE), Artificial Bee Colony (ABC), and other recently developed algorithms.
1.Introduction to Optimization -- 2.Jaya Optimization Algorithm -- 3.Application of Jaya Algorithm On Single Objective Unconstrained And Unconstrained Benchmark Functions -- 4.Application of Jaya Algorithm On Multi-objective Unconstrained And Constrained Benchmark Functions -- 5.Application of Jaya Algorithm On Constrained Benchmark Mechanical Design Problems -- 6.Single And Multi-objective Design Optimization of Different Types of Mechanical Elements Using Jaya Algorithm -- 7.Single And Multi-objective Design Optimization of Heat Exchangers Using Jaya Algorithm -- 8.Single and Multi-objective Design Optimization of Heat Sinks Using Jaya Algorithm -- 9.Single and Multi-objective Design Optimization of Mechanical Draft Cooling Towers Using Jaya Algorithm -- 10.Robot Path Planning Using Jaya Algorithm -- 11.Multiobjective Optimization of Design and Manufacturing Tolerances Using Jaya Algorithm -- 12.Single and Multiobjective Optimization of Traditional and Modern Machining and Nano-finishing Processes Using Jaya Algorithm -- 13.Single and Multiobjective Optimization of Advanced Casting Processes Using Jaya Algorithm -- 14.Applications of Jaya Algorithm to Different Engineering and Science Disciplines -- 15.Concluding Remarks -- Appendix: Jaya Algorithm Codes for Multiobjective Unconstrained and Constrained Optimization Problems.
Keywords: Computational intelligence; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Mathematical optimization; Mechanical engineering; Industrial engineering; Production engineering; Computational Intelligence; Engineering Thermodynamics, Heat and Mass Transfer; Optimization; Mechanical Engineering; Industrial and Production Engineering